Impact of Music on Mental Health - Pokharel, Ramesh (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Music affects our brain at different levels. Our mood changes with different types of music. However, at a very deep level, its effect is similar to that of deep meditation. The main objective of this study was to explore the impact of music on mental health. This paper explores, how daily listening and practising of music affects our body and mind. MATERIALS AND METHODS: Qualitative method based on personal experience and document review method was used in this research. Relevant and related literatures were searched through different search engines to draw the conclusion. RESULTS: Different systematic experimentations have shown that music practice cultivates the life of a human being. Music as yoga is a combination of breathing exercises and physical activities. CONCLUSIONS: Music has valuable, powerful and important role in happiness, managing mental stress, and for providing relief to the mind.